ALWI DAHLAN DALAM LINTASAN RISET DI JURUSAN ILMU KOMUNIKASI FISIP UNIVERSITAS BRAWIJAYA - Nisa Alfira; Sri Handayani (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2018)
Prof. M. Alwi Dahlan, Ph.D was the first Indonesian who became student of the founding fathers of communication science in USA. Alwi Dahlan got his degrees from USA. He received doctoral degree from University of Illinois, USA in 1967. He was a student of James W. Carey when he did his research for dissertation titled “Anonymous Disclosure of Government Information as Form of Political Communication”. Alwi Dahlan then came back to Indonesia and he was working in several institutions. He became important figure who promoted communication science in Indonesia. Department of Communication Science, Faculty of Social and Political Sciences Universitas Brawijaya, especially by Komunitas Pengkaji Komunikasi (Community of Communication Researchers), for the last three years has developing research areas, one of them was to do research about ideas of Alwi Dahlan (later will be written as AD). This paper will describe the results of the researches, in order to show the significance of AD’s ideas in communication science.